ERK5 negatively regulates Kruppel-like factor 4 and promotes osteogenic lineage cell proliferation in response to MEK5 overexpression or fluid shear stress. (4th March 2021) - Zhang, Bo; An, Liping; Geng, Bin; Ding, Ning; Coalson, Elam; Wan, Lang; Yan, Liang; Mohammed, Fawaz H. A.; Ma, Chongwen; Li, Rui; Yang, Xinxin; Zhang, Xiaohui; et al.
ABSTRACT: Aim of the study : Fluid shear stress (FSS) plays a critical role in osteoblast proliferation via extracellular signal-regulated kinase 5 (ERK5). Kruppel-like factor 4 (KLF4) knockout robustly enhances bone formation due to increased osteoblast differentiation and mineralization. However, the effect of KLF4 on osteoblast proliferation is unresolved. Therefore, the aim of our study was to investigate the effect of KLF4 on osteogenic lineage cell proliferation and the relationship between KLF4 and ERK5. Materials and methods : MC3T3-E1 cells were treated with FSS and/or KLF4 siRNA, cell viability was accessed by Edu labeling and CCK-8 assay, and proliferative gene expression were assessed by PCR array. Bone marrow stromal cells (BMSCs) were infected with adenovirus expressing KLF4 and/or constitutively active MEK5, cell viability was evaluated using crystal violet staining, colony formation assay, and cell WST1 assay. The levels of KLF4 and ERK5 phosphorylation were identified through qRT-PCR and western blot, respectively. Results : KLF4 expression was significantly down-regulated by FSS exposure, however, this was reversed by ERK5 siRNA. KLF4 overexpression inhibited colony formation efficiency and cell viability in BMSCs. Adenoviruses expressing constitutively active MEK5 increased ERK5 phosphorylation, which inhibited KLF4 expression, and promoted BMSC proliferation. FSS-induced osteoblast proliferation also involved elevation of Cyclin B2 and Cdc14b as well as repressed expression of P27. Conclusions : KLF4 negatively regulates osteogenic lineage cell proliferation, and ERK5 negatively regulates KLF4 expression and promotes osteogenic lineage cell proliferation.